The burden of unlawful use of opioid and associated epidemiological characteristics in Africa: A scoping review - Hope Onohuean; Frasia Oosthuizen (PLoS ONE, 2025)
Introduction There is an ongoing global upsurge of opioid misuse, fatal overdose and other related disorders, significantly affecting the African continent, due to resource-limited settings and poor epidemiological surveillance systems. This scoping review maps scientific evidence on epidemiological data on unlawful opioid use to identify knowledge gaps and policy shortcomings. Method The databases (PubMed, Scopus, Web of Sciences) and references were searched guided by Population, Concept, and Context (PCC) and PRISMA-ScR. The extracted characteristics examined were author/year, African country, epidemiological distribution, age group (year), gender, study design and setting, common opioid/s abused, sources of drugs, reasons for misuse, summary outcomes and future engagement. Results A population of 55132 participated in the included studies of 68 articles, with the largest sample size of 17260 (31.31%) in a study done in South Africa, 11281(20.46%) in a study from Egypt and 4068 (7.38%) in a study from Ethiopia. The gender of the participants was indicated in 65(95.59%) papers. The mean and median age reported in 57(83.82%) papers were 15.9-38, and 22-31years. The majority of study-designs were cross-sectional, 44(64.71%), and the most used opioids were heroin, 14articles (20.59%), tramadol, 8articles (11.76%), and tramadol & heroin, 6 articles (8.82%) articles. Study-settings included urban community 15(22.06%), hospital 15(22.06%), university students 11(16.18%), and secondary school learners 6(8.82%). The highest epidemiological distributions were recorded in the South African study, 19615(35.60%), Egyptian study, 14627(26.54%), and Nigerian study 5895(10.70%). Nine (13.24%) papers reported major opioid sources as black market, friends, and drug dealers. To relieve stress, physical pain and premature ejaculation, improve mood and sleep-related problems and help to continue work, were the major reasons for taking these drugs as reported in twenty articles (29.41%). Conclusion The findings of this scoping review show significant knowledge gaps on opioid usage in the African continent. The epidemiological distribution of unlawful use of opioids among young adults, drivers, and manual labourers in both genders is evident in the findings. The reason for use necessity scrutinises the role of social interaction, friends and family influence on illicit opiate use. Therefore, there is a need for regular epidemiological surveillance and investigations into multilevel, value-based, comprehensive, and strategic long-term intervention plans to curb the opioid problem in the region.